(untitled) (Journal of actual problems of jurisprudence, 2022)
The market economy formed in the Republic of Kazakhstan introduced a number of changes in the content of labour relations, in the legal situation of subjects of labour relations in connection with the emergence of new forms of ownership and the use of new methods of business. The absence of concrete effective measures in the field of legal regulation of labour relations, protection of the interests of labour relations participants, the imperfection of mechanisms for implementing social partnership leads to tension in social and labour relations. Therefore, in order to reduce social tensions arising from labour relations in the society life, there is a need to reform the existing legislation. It is clear that the current condition of legislative regulation of the procedure for considering and resolving labour relations, disagreements between the employee and the employer does not meet specific requirements for the protection of participants in labour relations. In this regard, the concept of legal policy until 2030 of the Republic of Kazakhstan emphasizes the need to reform labour relations with the help of flexible tools. The need to study the legal aspects of ensuring the implementation of citizens’ labour rights depends directly on changes and reforms in the economy, in the social and legal systems of the country. Keywords: personal labour rights; collective labour rights; right to social protection, legal guarantees, employee, employer, liability.